Direct oral anticoagulants in patients with hematologic malignancies. Issue 4 (29th July 2020) - Serrao, Alessandra; Fiori, Luciano; Santoro, Cristina; De Luca, Maria L.; Ferretti, Antonietta; De Luca, Giulia; Ligia, Silvio; Lapietra, Gianfranco; Mohamed, Sara; Breccia, Massimo; Chistolini, Antonio
Abstract: The anticoagulant treatment for patients with hematologic malignancies is low molecular weight heparin (LMWH), which is considered the safest in this particular patients setting. Although direct oral anticoagulants (DOACs) have proven their efficacy and safety in patients with cancer, their use can be challenging in patients with hematologic malignancies due to the peculiarity of these neoplasms: high thrombotic risk, possible onset of thrombocytopenia and concomitant anticancer therapies. The aim of our study was to evaluate the efficacy and safety of DOACs for venous thromboembolism or atrial fibrillation in patients with hematologic malignancies and plasmatic DOACs level during anticancer therapy and at time of bleeding or thrombotic complications. We evaluated patients with hematologic malignancies treated with DOACs for venous thromboembolism or atrial fibrillation—therapy was maintained until the platelet count was ≥50 × 10 9 /L. In case of concomitant anticancer treatment and haemorrhagic or thrombotic events, we checked DOACs plasma levels (trough and peak). The patients evaluated were 135: 104/135 were on anticancer therapy. We did not observe either thrombotic or major haemorrhagic adverse events. Minor bleedings occurred in 10 patients and clinical relevant non‐major (CRNM) in two patients. There was a statistically significant correlation between bleedings and myelodysplastic syndrome. DOACs resulted effective and safe in patients with hematologic malignancies. DOACs plasma level can be helpful in suggesting an early dose adjustment to prevent haemorrhagic adverse event in patients on concomitant anticancer therapy. Larger prospective studies including hematologic patients are warranted to confirm the safety and efficacy of DOACs.